Electrochemical Approaches for CO 2 Conversion to Chemicals: A Journey toward Practical Applications - Overa, Sean; Ko, Byung Hee; Zhao, Yaran; Jiao, Feng (Accounts of chemical research, 2022)
Carbon capture, utilization, and sequestration play an essential role to address CO emissions. Among all carbon utilization technologies, CO electroreduction has gained immense interest due to its potential for directly converting CO to a variety of valuable commodity chemicals using clean, renewable electricity as the sole energy source. The research community has witnessed rapid advances in CO electrolysis technology in recent years, including highly selective catalysts, larger-scale reactors, specific process modeling, as well as a mechanistic understanding of the CO reduction reaction. The rapid advances in the field brings promise to the commercial application of the technology and the rapid rollout of the CO electroreduction for chemical manufacturing.This Account focuses on our contributions in both fundamental and applied research in the field of electrocatalytic CO and CO reduction reactions. We first discuss (1) the development of novel electrocatalysts for CO /CO electroreduction to enhance the product selectivity and lower the energy consumption. Specifically, we synthesized nanoporous Ag and homogeneously mixed Cu-based bimetallic catalysts for the enhanced production of CO from CO and multicarbon products from CO, respectively. Then, we review our efforts in (2) the field of reactor engineering, including a dissolved CO H-type cell, vapor-fed CO three-compartment flow cell, and vapor-fed CO membrane electrode assembly, for enhancing reaction rates and scalability. Next, we describe (3) the investigation of reaction mechanisms using in situ and operando techniques, such as surface-enhanced vibrational spectroscopies and electrochemical mass spectroscopy. We revealed the participation of bicarbonate in CO electroreduction on Au using attenuated total-reflectance surface-enhanced infrared absorption spectroscopy, the presence of an "oxygenated" surface of Cu under CO electroreduction conditions using surface-enhanced Raman spectroscopy, and the origin of oxygen in acetaldehyde and other CO electroreduction products on Cu using flow electrolyzer mass spectrometry. Lastly, we examine (4) the commercial potential of the CO electrolysis technology, such as understanding pollutant effects in CO electroreduction and developing techno-economic analysis. Specifically, we discuss the effects of SO and NO in CO electroreduction using Cu, Ag, and Sn catalysts. We also identify technical barriers that need to be overcome and offer our perspective on accelerating the commercial deployment of the CO electrolysis technology.